2009
DOI: 10.1371/journal.pone.0006142
|View full text |Cite
|
Sign up to set email alerts
|

Rhythms of Consciousness: Binocular Rivalry Reveals Large-Scale Oscillatory Network Dynamics Mediating Visual Perception

Abstract: Consciousness has been proposed to emerge from functionally integrated large-scale ensembles of gamma-synchronous neural populations that form and dissolve at a frequency in the theta band. We propose that discrete moments of perceptual experience are implemented by transient gamma-band synchronization of relevant cortical regions, and that disintegration and reintegration of these assemblies is time-locked to ongoing theta oscillations. In support of this hypothesis we provide evidence that (1) perceptual swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
169
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 85 publications
(113 reference statements)
21
169
0
Order By: Relevance
“…Our results demonstrate that workspace formation is a fairly broadband or scale-invariant phenomenon: there is some evidence for task-related increases in global efficiency and physical distance, as well as task-related decreases in clustering and modularity, across all frequency intervals considered (collectively encompassing the range of 8 -120 Hz). This is compatible with various prior reports highlighting the significance of ␣-, ␀-, and ␄-band synchronization as mechanisms for communication between distributed neuronal groups (Rodriguez et al, 1999;Doesburg et al, 2009;.…”
Section: Complex Network and Workpace Theorysupporting
confidence: 93%
“…Our results demonstrate that workspace formation is a fairly broadband or scale-invariant phenomenon: there is some evidence for task-related increases in global efficiency and physical distance, as well as task-related decreases in clustering and modularity, across all frequency intervals considered (collectively encompassing the range of 8 -120 Hz). This is compatible with various prior reports highlighting the significance of ␣-, ␀-, and ␄-band synchronization as mechanisms for communication between distributed neuronal groups (Rodriguez et al, 1999;Doesburg et al, 2009;.…”
Section: Complex Network and Workpace Theorysupporting
confidence: 93%
“…This result is supported by three sources of evidence: (i) tau expression is densely expressed in frontal regions (see Fig. 1C) as previously reported (Goerdert et al, 1989;Trojanowski et al, 1989;Santa-Maria et al, 2005;McMillan et al, 2008), (ii) anatomical studies have demonstrated the existence of a monosynaptic pathway from the hippocampus to the frontal cortex (Swanson, 1981;Ferino et al, 1987;Thierry et al, 2000), and (iii) gamma-band synchronization between distant brain regions, including the frontal lobe, has been involved in a variety of cognitive processes, such as perception, attentional selection, and memory (Desmedt and Tomberg, 1994;Von stein et al, 2000;Doesburg et al, 2008Doesburg et al, , 2009Sehatpour et al, 2008). Combining more specific cognitive tests with long-range gamma synchronization measurements could be a more adequate approach at providing novel insights into the role of tau in cognitive functions.…”
Section: Discussionsupporting
confidence: 78%
“…However, an alternative interpretation is possible since several authors propose that the prefrontal cortex does not maintain mnemonic representations (Lebedev et al, 2004;Owen et al, 1998;Petrides, 2000;Rissman et al, 2008;Rowe and Passingham, 2001). Instead, prefrontal cortex is considered to participate in controlled processing of the activity of posterior brain regions more directly involved in representing specific features as well as categorical information (Doesburg et al, 2009;Grimault et al, 2009;Kessler and Kiefer, 2005;Mechelli et al, 2004;Rainer and Ranganath, 2002;Serences and Yantis, 2006). This control could be exerted by means of longrange fronto-posterior connections (Grimault et al, 2009;Hasegawa et al, 2000;Kessler and Kiefer, 2005).…”
Section: Discussionmentioning
confidence: 99%